Please answer Q1 please

Dear student,
Let P(n): n(n+1)(n+5) is a multiple of 6Step IWe have, P(1): 1(1+1)(1+5)=1×2×6=12=6×2  is a multiple of 6P(1) is true.Step IILet P(m) be true. Then,m(m+1)(m+5) is a multiple of 6m(m+1)(m+5)=6λ   for some λN    ..(1)Now, we shall show that P(m+1) is true. For this we have to show  that(m+1)(m+2)m+6 is of 6We have,(m+1)(m+2)m+6=(m+1)(m+2)m+5+1=(m+1)(m+2)m+5+(m+1)(m+2)=m(m+1)(m+5)+2(m+1)m+5+(m+1)(m+2)=6λ+2(m+1)m+5+(m+1)(m+2)After this it is getting difficult to solve as the last two terms should be same . Here it seems there should be some correction in the question.
Regards

  • 0
Solution....

  • 1
What are you looking for?